Early-Life Parent–Child Relationships and Adult Children's Support of Unpartnered Parents in Later Life. (8th February 2018) - Lin, I-Fen; Wu, Hsueh-Sheng
Abstract: Objectives: The proportion of older adults who are unpartnered has increased significantly over the past 25 years. Unpartnered older adults often rely on their adult children for support. Most previous studies have focused on proximal factors associated with adult children's support of their parents, while few have examined distal factors, such as parent–child relationships formed during childhood. This study fills the gap by investigating the direct and indirect associations between early-life parent–child relationships and adult children's upward transfers to unpartnered parents. Method: Data came from two supplements to the Panel Study of Income Dynamics, in which respondents were asked about their relationships with mothers and fathers before age 17 and their transfers of time and money to parents in 2013. Path models were estimated for unpartnered mother–adult child dyads and father–adult child dyads separately. Results: For adult children of unpartnered mothers, psychological closeness has a direct, positive association with time transfer, while physical violence has an indirect association with time transfer through adult children's marital status. For adult children of unpartnered fathers, psychological closeness has neither a direct nor an indirect association with time or money transfer, but physical violence has a direct, negative association with time transfer. Discussion: Early-life parent–child relationships play a pivotal role in influencing adult children's caregiving behavior, both directly and indirectly. Our findings suggest that by improving their relationships with children early in life, parents may be able to increase the amount of time transfer that they receive in late life.